Cover Picture: Contrib. Plasma Phys. 2‐3/2018. Issue 2 (25th March 2018) - Unknown
Abstract : Real part of a spin‐density response function. The particle‐hole bands are shown with gray solid lines; white arrows denote the majority and minority spins in these continua. Energies and wave vectors are given in reduced as well as in real units for a typical GaAs/AlGaAs structure. Figures 1 of the paper by D. Kreil et al.